Value management implementation in construction : a global view - Oke, Ayodeji Emmanuel; Stephen, Seyi Segun; Aigbavboa, Clinton Ohis (Emerald Publishing Limited, 2022)
Value management has been applied to construction projects throughout the world, but in some regions, it is just gaining popularity. Therefore, it is necessary to create awareness of value management among stakeholders and understand various obstacles to its implementation. Value Management Implementation in Construction addresses various factors that can enhance the application of the discipline as well as its adoption among concerned stakeholders. This book discusses the practice of value management in various developed and developing countries by exposing the techniques and models that can be employed in value management exercises, with a view to achieving sustainable development while delivering projects to the satisfaction of clients. This book provides guidance on value management as a tool for improving the delivery of infrastructural projects for construction professionals, employers of labour, researchers and students alike with evidence from various countries around the world.
Keywords: Value analysis (Cost control); Valuation.; Business & Economics -- Corporate Finance / Valuation.; Finance.; elektronické knihy; electronic books